Effect of 3D random pitting defects on the collapse pressure of pipe — Part I: Experiment. (August 2018) - Wang, Huakun; Yu, Yang; Yu, Jianxing; Duan, Jinghui; Zhang, Yu; Li, Zhenmian; Wang, Caimei
Abstract: This paper is aimed at assessing the effects of local random external pitting defects on the collapse pressure of pipe under external pressure. In this two-part paper series, the buckling performance of locally random corroded pipe was experimentally and numerically studied. The experimental program described in Part I involves seamless carbon steel tubes with D/t  = 17 and with different size of pitting defects. The random pitting defects were introduced into the outside surface of pipe using 6% FeCl3 solution and then the collapse pressure of such locally random corroded pipe was obtained experimentally. The profile of pipe was examined in details using Hexagon's new RA7320 Portable Arm Coordinate Measuring Machine (PACMM) and the measured data were analyzed meticulously. It indicated that either the out-of-roundness imperfection shape n  = 2 or n  = 3 fits best with the measure data. The characteristics of random pitting corrosion were statistically analyzed and the mass loss of pipe due to pitting corrosion was also determined after buckling test, the analysis results indicate that both lognormal and generalized extreme value (GEV) distribution are adequate to depict the distribution of pitting depth and pitting diameter-to-depth ratio (DDR). The corrosion morphology was observed using scanning electron microscope (SEM), which indicates that the shape of pitting defect is cylindrical or semi-ellipsoid. Finally, the relationship between collapse pressure and geometry defects was analyzed based on the experiment results. Highlights: The buckling behavior of locally random corroded pipe (external corrosion) was experimentally investigated. A 2-wave out-of-roundness imperfection shape shows a better fit of the seamless carbon steel pipe profile. Both lognormal and GEV distribution are adequate to describe the distribution of pitting depth and diameter-to-depth ratio. A shallow-and-wide cylindrical-shaped or semi-ellipsoidal-shaped pit is more representative of the pitting defects. The collapse pressure of pipe is significantly affected by corrosion defects and out-of-roundness.